STRATEGI MENINGKATKAN KEUNGGULAN DAYA SAING PRODUK UMKM DI KABUPATEN SUMBAWA MELALUI KAPABILITAS PEMASARAN DAN ORIENTASI PASAR - Kurniawansyah, K; Pamungkas, Binar Dwiyanto; Ardayensy, Meisi (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to determine strategies to increase the competitive advantage of MSME products in Sumbawa District through marketing capabilities and market orientation. The type of this study was associative study which aims to examine the effect of marketing capabilities (X1) and market orientation (X2) on the competitive advantage of MSME products in Sumbawa District (Y). The type of data used in this study was quantitative obtained directly from primary sources using a research instrument in the form of a questionnaire. The respondents in this study were 68 MSME actors in Seketeng Village. Determination of respondents in this study used a probability sampling technique with the simple random sampling method. The data used in this study was processed using the SPSS application to be analyzed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination testing (R2). The results of this study indicate that marketing capabilities and market orientation had a positive and significant effect on the competitive advantage of MSME products in Sumbawa District, both partially and simultaneously. The contribution of marketing capabilities and market orientation in effecting the competitive advantage of MSME products in Sumbawa District was 41.7%, while the remaining of 58.3% was effected by other variables outside this research model, such as product quality, price, marketing strategy, and regulations.